An existential-phenomenological explication of being-a-black student at a predominantly white university, with special reference to Rhodes University - Harilall, Rehena Ranir (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
This study attempts to explore, theoretically and empirically, the experience of being black in a predominantly white university. It is more specifically concerned with perceived interaction between members of different cultural and ethnic groups, namely, between black and white. Using the existential-phenomenological method the experience of seven subjects, both male and female, were explicated. This explication revealed that black students become aware of their "difference" during interaction with members of the dominant white group. The black students perceive the behaviour of the white-dominant group to be racist and this creates a great deal of latent hostility, anger, and resentment. It is suggested that a programme be developed to diffuse the conflict situation during intergroup interaction at university.
Keywords: Racism; South Africa; Black university students; College; Racism -- South Africa -- Psychological aspects; College students, Black; College students, Black -- South Africa -- Psychology